A study on Santali rhymes: collection and discussion - Murmu, Jogendranath (Yayasan Mitra Persada Nusantara, 2023)
The ancestors of the Santals are the largest ethnic community in India. Santali is their mother tongue, is origin from an Austro-Asiatic language family. Santali is the rich heritage of folk rhymes. In Santali folk literature, however, rhyme holds a place of equal importance to these other forms. The aims of the study mainly focused on Santali rhymes that were intimately related to the social and cultural life of the Santal community. In this view, to obtain a profile of the culture-related folklore, the study was done on the qualitative linguistic approach. The result showed that the theoretical perspective of cultural materialism, the argument of Santali folk rhyme is created in the Santali language based on orality laid the conservation of the Santal-socio-cultural system. Santali folk rhymes are set in the context of Santal tradition, culture, behavior, social status, and identity construction within the community.